Riflessioni sui bisogni formativi per professionisti impegnati nella lotta alla violenza maschile nelle relazioni affettive in Basilicata - Pasquale Emanuele De Girolamo; Grazia Moffa; Marco Di Gregorio (Culture e Studi del Sociale)
The article analyzes the main results of an exploratory research conducted between April 2022 and September 2023 as part of a project funded by the Basilicata Region within the regional strategy for combating gender-based violence, named the “CPM 4.0 project, Cen-ter for the Prevention of Abuse”. This study examines the training requirements of social workers and professionals operating in the field of combating male intimate partner violence. By looking at the specific skill sets, knowledge bases, and resources necessary for effectively addressing such complex issues, it offers valuable insights for enhancing the capacity of practitioners in this critical area of intervention.